Cellulose isolation from leucaena leucocephala seed: effect on concentration sodium hydroxide / Nur Aini Nabilah Ab Rashid... [et al.] - Ab Rashid, Nur Aini Nabilah; Husin, Maryam; Yury, Norjanah; Othman, Monarita; Mohd Shariff, Zarila; Kassim, Haliza; Li, Abd Rashid (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The isolation of cellulose fibres requires the removal of other components such as lignin, hemicellulose, and pectin from the biomass. In this study, the matured Leucaena leucocephala seeds (LLS) was applied as a raw material to extract cellulose. The influence of sodium hydroxide concentration (2% - 6%) on the structure of cellulose isolated LLS was studied. The highest yield 23.7% of cellulose was extracted using 4 wt% NaOH treatment. The chemical-physical properties of cellulose extracted were characterized using Fourier Transform Infrared (FTIR), Field Emission Scanning Electron Microscope (FESEM) and X-ray Diffraction (XRD). FTIR spectrum indicated that of all treated samples shows the peaks of cellulose structure. The highest crystallinity index of cellulose was obtained from 6% NaOH treatment which is 76.04%. Under FESEM images, the cellulose appeared in fibrils-like structure. The cellulose obtained can be further disintegrate to micro and nano cellulose to increase the chemical physical properties for various application such as in biocomposite, biomedicine and other value-added chemicals.